VIOLATION OF THE EXERCISE OF THE PROFESSION: analysis of the vulnerable situation in which women journalists find themselves. (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The 21st century, marked by a technological society under constant surveillance, can also be characterized as the context for the emergence of major “fake news”, whose contents are easily disseminated instantly through digital platforms. It is within this context in which the role of the journalism professional ends up gaining social relevance to investigate and convey, through the mass media (television and internet), the veracity of information conveyed informally. However, the search for information does not, in practice, prove to be such an easy task to carry out and, when it comes to women journalists, the issue ends up becoming even more complex given the greater vulnerability of women in relation to men in terms of journalistic performance. At this stage, the present study aims to present.Keywords: Journalism; freedom of expression; violence against women.